2023
DOI: 10.1136/bmj-2022-073711
|View full text |Cite
|
Sign up to set email alerts
|

Communication of anticancer drug benefits and related uncertainties to patients and clinicians: document analysis of regulated information on prescription drugs in Europe

Abstract: ObjectiveTo evaluate the frequency with which relevant and accurate information about the benefits and related uncertainties of anticancer drugs are communicated to patients and clinicians in regulated information sources in Europe.DesignDocument content analysis.SettingEuropean Medicines Agency.ParticipantsAnticancer drugs granted a first marketing authorisation by the European Medicines Agency, 2017-19.Main outcome measuresWhether written information on a product addressed patients’ commonly asked questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Research shows, however, that physicians often misinterpret the robustness of evidence used for regulatory decision-making by the FDA, leading to overestimated benefits and underestimated risks (23,(25)(26)(27). Moreover, uncertainties about the benefit-risk balance are seldom communicated by regulators to physicians, patients, or the public (28).…”
Section: Informed Consent and Poor Understanding Of Cmamentioning
confidence: 99%
“…Research shows, however, that physicians often misinterpret the robustness of evidence used for regulatory decision-making by the FDA, leading to overestimated benefits and underestimated risks (23,(25)(26)(27). Moreover, uncertainties about the benefit-risk balance are seldom communicated by regulators to physicians, patients, or the public (28).…”
Section: Informed Consent and Poor Understanding Of Cmamentioning
confidence: 99%
“…Research by Courtney Davis and colleagues on new cancer drugs approved by the European Medicines Agency is concerning on this front (doi:10.1136/bmj-2022-073711). 1 The study found that important information about the benefits of cancer drugs was not included in patient leaflets and that concerns about the reliability of evidence for these benefits were omitted in communication to clinicians and patients.…”
mentioning
confidence: 99%